Variation of the Lexical Item Libélula in the Data of the Linguistic-Ethnographic Atlas of the Acará Valley (ALEVA) (Interdisciplinary Studies Journal, 2024)
This study aims to describe and map the linguistic variation of the lexical item libélula (dragonfly) in the data from the Linguistic-Ethnographic Atlas of the Acará Valley (ALEVA) project, with special attention to Portuguese in contact with the Tembé and Japanese languages, as well as the variety of quilombola Portuguese in the region. The theoretical-methodological framework guiding this study was based on Geosociolinguistics (RAZKY, 1998) and Multidimensional and Relational Dialectology (RADTKE; THUN, 1998). The data were collected on-site through the application of the Semantic-Lexical Questionnaire (QSL), developed by the National Committee of the Linguistic Atlas of Brazil (ALiB, 2001). Six participants were interviewed at each of the six survey points, totaling 36 participants, stratified by gender (male and female) and age (10-12, 18-40, and 50-75 years, all with schooling up to the elementary level). The results point to the existence of diaectal influences in the lexical variation recorded from the mapping of the lexical item libélula.
Keywords: ALEVA; Geosociolinguistics; Pluridimensional and Relational Dialectology